2015
DOI: 10.1530/erc-15-0192
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine promotes ovarian cancer cell proliferation through the mTOR/S6 pathway

Abstract: Glutamine is one of the main nutrients used by tumor cells for biosynthesis. Thus, targeted inhibition of glutamine metabolism may have anti-tumorigenic implications. In the present study, we aimed to evaluate the effects of glutamine on ovarian cancer cell growth. Three ovarian cancer cell lines, HEY, SKOV3, and IGROV-1, were assayed for glutamine dependence by analyzing cytotoxicity, cell cycle progression, apoptosis, cell stress, and glucose/glutamine metabolism. Our results revealed that administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 56 publications
(53 reference statements)
1
76
0
1
Order By: Relevance
“…This resulted in a more aggressive behavior as evidenced in higher proliferation rate and increased tumor growth (42). A correlation between glutamine dependency and increased aggressiveness was also seen in ovarian cancer, where it was shown that glutamine is required to promote cell proliferation (43). In addition, it was demonstrated that certain ovarian cancer cell lines are glutamine-dependent while others are glucose dependent, and importantly, glutamine dependency correlated with migration and invasiveness (44).…”
Section: Discussionmentioning
confidence: 93%
“…This resulted in a more aggressive behavior as evidenced in higher proliferation rate and increased tumor growth (42). A correlation between glutamine dependency and increased aggressiveness was also seen in ovarian cancer, where it was shown that glutamine is required to promote cell proliferation (43). In addition, it was demonstrated that certain ovarian cancer cell lines are glutamine-dependent while others are glucose dependent, and importantly, glutamine dependency correlated with migration and invasiveness (44).…”
Section: Discussionmentioning
confidence: 93%
“…In a previous report, glutamine promoted ovarian cancer cell proliferation through the mTOR/S6 pathway, suggesting a close association between amino acid metabolism and the mTOR signaling pathway (40). ASCT2 mediates the uptake of glutamine in tumors.…”
Section: Univariate Analysismentioning
confidence: 83%
“…The primary source of nutrition that provides bioenergy in cancer cells to proliferate is glutamine. [24] The increasing of glutaminolysis is one of the characteristics of metabolic changes in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…[25] In cancer cells, the conversion of glutamine to lactate has increased compared to healthy cells. [24] Because of its essential function in cancer cell metabolism, if glutamine deficiency occurs, cell growth inhibition can even induce apoptosis. [24] Yang et al found that the level of cancer cell dependence on glutamine was highly correlating with the rate of cancer invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation